Pengaruh Focusky Sebagai Media Pembelajaran pada Mata Pelajaran Bahasa Indonesia untuk Meningkatkan Minat Belajar Siswa Kelas VIII di SMP Negeri 2 Kadugede - Pranaya, Daffa Raihan; Gustiana, Eva (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Indonesian language learning in schools generally still relies on textbooks and lecture-based methods, making it seem monotonous and less engaging for students. This study aims to enhance students’ learning interest by using Focusky as an instructional medium. The research employed a quantitative method with a Pretest-Posttest Control Group Design and was conducted at SMP Negeri 2 Kadugede. The research subjects were students of class VIII A (27 students) and class VIII B (26 students). Data were collected through observation, interviews, and questionnaires. The data is analyzed using quantitative descriptive methods. The study is expected to improve students’ learning outcomes and provide benefits for both teachers and the school. The analysis results show that the average learning interest of students using Focusky media is 37.54, higher than the class without this media, which is 25.38. This difference of 12.16 points is statistically significant (p = 0.000). The Paired Samples T-Test also shows a significance value of 0.000 (< 0.05), meaning there is a significant difference in learning interest between the two groups. It can be concluded that H1 is accepted and H0 is rejected. These findings prove that the use of Focusky is effective in increasing the learning interest of Indonesian language students at SMP Negeri 2 Kadugede